DETERMINAN KONSUMEN DALAM PEMBELIAN RUMAH (KPR) DEVELOPER SYARIAH - Feri Irawan (widya balina, 2019)
In this modern age, homes are becoming an increasingly increasing number of basic needs for society. However, critical urban middle communities begin to adopt an Islamic lifestyle by utilizing a sharia-based mortgage facility on sharia housing provided by the Developer Property. The purpose of this study is to determine the influence of religious conformity factors and operational factors on consumers in purchasing home mortgages developer sharia. The research method used is multiple linear regression sourced from the primary data by distributing questionnaires to home consumers KPR developer sharia as much as 90 respondents. Sampling technique used is purposive sampling technique and data using SPSS software version 22 for windows. The results of this study indicate that religious conformity factors partially no significant effect on the purchase of home mortgage developer sharia with Sig value. (0.154> 0.05) and the value of t-count (-1.439 <1.987). Operational factors partially no significant effect on the purchase of home mortgages developer sharia with Sig value. (0.416> 0.05) and the value of t-count (0.818 <1.987). While simultaneously between the factors of religious suitability and operational factors also stated no effect on the variable home mortgages developer sharia.